Exploring clinicians' awareness of language line and barriers in accessing NHS interpreting services - Maria Irimia; Trusha Kolke; Antony Cyriac; Cristina Cepraga; Giulio Romani; Aleksandra Bieluczyk; Pushpashtree Krishnamurthy; Nusrat Azmi; Mina Saeed (Future Healthcare Journal)
Background: According to the latest 2021 Census data, 5.1 million people (8.71%) living in England and Wales do not speak English as their first language, an increase by 0.9 million compared to 2013.1,2 1.47% of the population speaks limited English, whilst 0.26% do not speak English at all.1 Language barriers are known to increase vulnerability and they contribute significantly to health inequalities, resulting in poor health outcomes.2,3 As part of the 2010 Equality Act, the National Health Service (NHS) has recognised the complexities of caring for a multicultural population, and has adopted several principles and legislations, including language support services, to improve the health outcomes of non-native English-speaking patients. Therefore, all NHS patients are entitled to language interpreting services, whilst healthcare professionals have to respect and promote this right.4 Aim and methods: This audit assessed clinicians’ awareness of language line services available in our trust, and explored several limitations in using these services. Data were collected using an online structured questionnaire, and analysed using Excel. Results: Forty-six clinicians completed the questionnaire. Twenty-seven (58.7%) were doctors working at F2/SHO levels. Twenty-five (54.3%) were working in a medical specialty. Thirty-three (71.8%) were aware of language line services, and 44 (95.6%) agreed that language barriers and cultural differences can impact patient care. Thirty-one (67.4%) reported having at least one clinical encounter with a non-native English-speaking patient at least once a month. Four (8.7%) reported always using language line, and eight (17.4%) used it often. Twenty-one (45.6%) used the language line rarely, whilst 13 (28.3%) never used it. Forty-four (95.6%) reported they often used friends and relatives to interpret, whilst thirty-five(76.1%) used online translating platforms.Twenty-five (54.3%) would use the language line for patients who do not speak English at all, and 22 (47.85) for patients with limited English. Only nine (19.5%) would offer the services to patients who seemed to understand English, without speaking it well. Eighteen (39.1%) would use the language line if friends or relatives were unable to translate, whilst eight (17.4%) would use it for safeguarding concerns. Nineteen (41.3%) would use the language line in all of the above situations.Factors limiting its usage included inability to find information about the service or not knowing how it works in 20 (43.4%) cases. Other obstacles included the length of the process (25,54.3%), long waiting lines (22,47.8%), lack of available phones on the wards (20,43.4%) and reduced number of languages available (13,28.2%). Eleven (23.9%) mentioned convenience, whilst seven (15.2%) did not feel encouraged by their senior colleagues to access the service. Conclusion: Although NHS language line services have been available for a long time, in reality they are not consistently being used, due to important limiting factors and lack of awareness. This audit highlights the importance of promoting language line services within NHS hospitals and advocating for non-native English-speaking patients’ rights, as a way to improve their health outcomes and achieve health equity.